Inclusion of Alcoholic Associations Into a Public Treatment Programme for Alcoholism Improves Outcomes During the Treatment and Continuing Care Period: A 6-Year Experience. (26th October 2017) - Rubio, Gabriel; Marín, Marta; Arias, Francisco; López-Trabada, José Ramón; Iribarren, Martín; Alfonso, Susana; Prieto, Raquel; Blanco, Agustín; Urosa, Belén; Montes, Victoria; Jurado, Rosa; Jiménez-Arriero, Miguel Ángel; et al.
Abstract: Aims: To investigate whether inclusion of self-help groups into the hospital treatment programme improves the prognosis of alcohol dependence through the treatment period; and to examine therapeutic adherence and prognosis during continuing care. Method: Patients attending the treatment programme at the 'Hospital 12 de Octubre' were randomized into two groups. In Group A ( n = 123), patients received the usual treatment included in our programme, whereas in Group B ( n = 126), patients also attended self-help groups. Patients were assessed with psychological scales at baseline, at the end of the treatment period and after completing the continuing care visits. Data were collected over a total of 6 years. Results: During the treatment period, patients in Group B accumulated more months of abstinence and dropped out less. During continuing care, patients in Group B accumulated more months of abstinence and therapeutic adherence was higher. Variables that were associated with these results during the continuing care period were: visits to the GP, scores on anxiety, impulsivity and meaning of life scales, and belonging to the group that attended the alcoholic associations. Conclusions: Mutual help groups incorporated into a public treatment programme appear to improve outcomes during treatment and on into continuing care. This experience supports cooperation between public health centres and alcoholic associations in treating alcoholism. Short Summary: Including alcoholic associations into the public treatment programme for alcoholism of the 'Hospital 12 de Octubre' in Madrid was shown to be associated with better outcomes in terms of months of accumulated abstinence, dropout rates and therapeutic adherence, during the treatment and continuing care periods.